1992
DOI: 10.1103/physrevb.46.9446
|View full text |Cite
|
Sign up to set email alerts
|

Soft-x-ray-emission studies of bulkFe3Si, FeSi, andFeSi2, and i

Abstract: Bulk iron silicides and implanted iron silicides have been studied by soft-x-ray emission (SXE) spectroscopy. The Si L2 3 emission spectra of these materials are measured. For bulk silicides, these spectra provide a measure of sand d-type partial density of states (PDOS) localized on the Si sites. We compare them with available band-structure calculations and also with photoemission measurements.For implanted systems, the Si L» emission spectra provide useful information about the silicide formation process wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…22,23 The bonding in the calcium silicides has been also explained as a general hybridization between the Ca s-p-d and Si s-p states. 24 The theoretical partial density of state with the Si-s, Si-p, and Si-d electronic states for ␤-FeSi 2 , 36,37 in which the positive chemical shift of Si L 2,3 was reported, 38 indicated that the ratio of the number of Si s, p, and d states was about 3:5:1. Thus, we can neglect the role of the Si 3d orbital in Cau Si chemical bonding.…”
Section: Resultsmentioning
confidence: 96%
“…22,23 The bonding in the calcium silicides has been also explained as a general hybridization between the Ca s-p-d and Si s-p states. 24 The theoretical partial density of state with the Si-s, Si-p, and Si-d electronic states for ␤-FeSi 2 , 36,37 in which the positive chemical shift of Si L 2,3 was reported, 38 indicated that the ratio of the number of Si s, p, and d states was about 3:5:1. Thus, we can neglect the role of the Si 3d orbital in Cau Si chemical bonding.…”
Section: Resultsmentioning
confidence: 96%
“…7c) gives insight into the Si L 2,3 soft x-ray emission (SXE) spectrum of Fe 3 Si reported by Jia et al 43 The SXE data from Fe 3 Si (see Fig. 1 of Jia et al) display three distinct peaks centered at binding energies of 2 eV, 6 eV, and 10 eV.…”
Section: B Ordered Compound Fe 3 Simentioning
confidence: 81%
“…Inelastic scattering spectra for semiconductors and insulators have been obtained especially for the light elements, such as B, C, N, O, Si, S, Al, Mg, and P. So far, resonant (and normal) emission spectra have been analyzed for graphite (Carlisle, Shirley, et al, 1995, 1999Skytt et al, 1994), Si (Rubensson et al, 1990;Ma et al, 1993;Miyano et al, 1993;Eisebit et al, 1996;Shin et al, 1996), MgO, Al 2 O 3 , and SiO 2 (O'Brien, Jia, Callcott, Rubensson, et al, 1991;O'Brien et al 1992O'Brien et al , 1993aO'Brien et al , 1993bO'Brien et al , 1993, B 2 O 3 and silicides (Jia et al, 1991(Jia et al, , 1992, Li halides (Tsang et al, 1987), cBN (Agui et al, 1997;Hanamura et al, 1997), hBN (Muramatsu et al, 1993;Jia et al, 1996), CdS and ZnS (Zhou et al, 1997), diamond (Ma et al, 1992), CaF 2 (Rubensson et al, 1994a(Rubensson et al, , 1994bJia et al, 1998), CaSi x (Jia et al, 1995), Al x Ga 1Ϫx As (Dong et al, 1992), Al x Ga 1Ϫx N (Duda, Stagarescu, et al, 1998), C 60 (Luo et al, 1995;Guo, Glans, et al, 1995), Y 2 O 3 (Mueller et al, 1996), and GaN (Stagarescu et al, 1996).…”
Section: A Experimental Datamentioning
confidence: 99%